2018
DOI: 10.1007/s00167-018-5299-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive Oxford unicompartmental knee arthroplasty ensures excellent functional outcome and high survivorship in the long term

Abstract: Purpose Whether unicompartimental or total knee arthroplasty is superior for treatment of anteromedial knee osteoarthritis, is still uncertain. Therefore, the purpose of this study was to evaluate clinical and radiological outcome as well as long-term survivorship of medial Oxford unicompartmental knee arthroplasty (OUKA) at an independent center with a minimum follow-up of 10 years. Methods This single-center retrospective cohort study reports the 10-15 years follow-up results of 113 consecutive patients (126… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 23 publications
2
18
1
3
Order By: Relevance
“…In addition, patients regain better ROM, return to activities quicker, have shorter hospital stays, gain superior function, and have a more natural feel of the knee after UKA[ 12 ]. The Oxford UKA is a type of mobile-bearing UKA and common for treating anteromedial OA of the knee[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, patients regain better ROM, return to activities quicker, have shorter hospital stays, gain superior function, and have a more natural feel of the knee after UKA[ 12 ]. The Oxford UKA is a type of mobile-bearing UKA and common for treating anteromedial OA of the knee[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It includes fixed-bearing UKA and mobile-bearing UKA. The Oxford UKA is a type of mobile-bearing UKA and a successful treatment for end-stage, symptomatic anteromedial OA of the knee[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…UKA can effectively relieve pain and improve function by surface replacement of the affected compartment and has the advantages of minimal trauma and a quick recovery. The long-term and medium-term functional results are satisfactory [1][2][3]. However, the contraindications of UKA are still controversial.…”
Section: Introductionmentioning
confidence: 97%
“…UKA can effectively relieve pain and improve function by surface replacement in the lesion compartment. It has the advantages of minimal trauma and rapid recovery, and the longterm and medium-term curative effects are satisfactory [1][2][3]. However, most UKA components currently used in China are designed for the physique of Western individuals, and many studies have shown that components designed for Western patients are not matched for other populations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%